Participants in a peer-based nutrition and health program in Zimbabwe value dialogue, peer support, and tangible action: A qualitative exploration of peer group experiences. - S Riley Auer; Newton Matandirotya; Prince Mathe; Musawenkosi Moyo; Lisa Sherburne; Katherine L Dickin (PLOS Global Public Health)
Peer support groups are implemented globally, and viewed as cost-effective, scalable platforms for delivering health and nutrition programming. Quality is important for participation and achieving social and behavior change goals. Little research has explored the perspectives of peer group participants on quality. This manuscript describes community-based implementation research, and associated findings, which was conducted to learn how participants of a nutrition and health program define quality peer groups and how they suggest improving peer groups. In-depth interviews on experiences, benefits, and challenges were conducted with participants of health and nutrition peer groups, including group members (n = 64) and facilitators (n = 30), in three districts in Zimbabwe. Qualitative data were analyzed thematically and preliminary results were presented in six follow-up focus group discussions with interviewees to provide input on results and interpretation. Peer groups met some of participants' needs for knowledge, social support, and visible improvements in their lives and homes. Participants described generally positive experiences that sustained participation and motivated behavior change. They highlighted group dynamics, interactive facilitation, and community recognition which support the credibility and motivation of group facilitators. Implementation could be improved by strengthening family engagement and more hands-on learning for encouraging participation. Local adaptation of group activities can address influences on behavior change and increase relevance to participants' needs. The perspectives of core stakeholders are essential to understand what aspects of peer groups are most important to implement the approach with quality across contexts. Implementation research and continued monitoring to understand participant perspectives should be an integral part of all programs to ensure the application of adult learning principles and an appropriate balance between fidelity and adaptation for local relevance and engagement.